2020
DOI: 10.3389/fchem.2020.00302
|View full text |Cite
|
Sign up to set email alerts
|

Ternary All-Polymer Solar Cells With 8.5% Power Conversion Efficiency and Excellent Thermal Stability

Abstract: All-polymer solar cells (all-PSCs) composed of polymer donors and acceptors have attracted widespread attention in recent years. However, the broad and efficient photon utilization of polymer:polymer blend films remains challenging. In our previous work, we developed NOE10, a linear oligoethylene oxide (OE) side-chain modified naphthalene diimide (NDI)-based polymer acceptor which exhibited a power conversion efficiency (PCE) of 8.1% when blended with a wide-bandgap polymer donor PBDT-TAZ. Herein, we report a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…Encouragingly, the maximum PCE up to 11.76 % was achieved by N2200‐based all‐PSCs, which was fully comparable to the highest PCE of fullerene‐based PSCs for the first time [5] . However, NDI‐based polymers including N2200 exhibited low light absorption coefficients in the near‐infrared (NIR) region, which significantly limited the short‐circuit current density ( J sc ) and further PCE enhancement of the resulting all‐PSCs [4a,d,6a,b,c,d] . Therefore, a few D‐A type conjugated polymers based on new building blocks with strong electron affinity such as bithiophene imide, [7a,b,c] double B←N bridged bipyridine, [8a,b] and 5,6‐dicyano‐2,1,3‐benzothiadiazole (DCNBT) [9a,b] were developed for use as polymer acceptors in all‐PSCs.…”
Section: Introductionmentioning
confidence: 92%
“…Encouragingly, the maximum PCE up to 11.76 % was achieved by N2200‐based all‐PSCs, which was fully comparable to the highest PCE of fullerene‐based PSCs for the first time [5] . However, NDI‐based polymers including N2200 exhibited low light absorption coefficients in the near‐infrared (NIR) region, which significantly limited the short‐circuit current density ( J sc ) and further PCE enhancement of the resulting all‐PSCs [4a,d,6a,b,c,d] . Therefore, a few D‐A type conjugated polymers based on new building blocks with strong electron affinity such as bithiophene imide, [7a,b,c] double B←N bridged bipyridine, [8a,b] and 5,6‐dicyano‐2,1,3‐benzothiadiazole (DCNBT) [9a,b] were developed for use as polymer acceptors in all‐PSCs.…”
Section: Introductionmentioning
confidence: 92%
“…In general, the active layers of ternary OSCs consist of two host components (electron donor/acceptor pairs [D/A]) and a third guest component, where the third component can be materials such as polymers, [29][30][31] small molecules, [32,33] dyes, [34] or nanoparticles. [35,36] Depending on the function of the third component, ternary OSCs can be classified into three categories: 1) two D/one A (D 1 /D 2 /A), 2) one D/two A (D/A 2 /A 1 ), and 3) D/nonvolatile additive/A (D/NVA/A).…”
Section: Role Of the Third Component During The Photovoltaic Processmentioning
confidence: 99%
“…A number of research efforts focus on increasing the stability of ternary OPVs through the careful selection and optimization of appropriate materials in ternary devices. Recently, Liu et al reported an 8.5% efficiency for a ternary device based on naphthalene di-imide polymer acceptor, in a blend with the polymer donors PBDT-TAZ and PTB7-Th [130]. This device exhibited high thermal stability, retaining 98% of its efficiency, after 300 h of heating at 65°.…”
Section: Organic Solar Cellsmentioning
confidence: 99%